Peningkatkan Perilaku Pasien dalam Tatalaksana Diabetes Melitus Menggunakan Model Behavioral Sistemral Sistem Model - Nur Aini; Widati Fatmaningrum; Ah. Yusuf (Jurnal Ners, 2011)
Introduction: Diabetic treatment need a very long time that make most of patient doesn’t obey. One of the methods can be used to improve patient’s compliance is nursing care model Behavioral System by Dorothy E. Johnson with its interventions are motivation and education. The objective of this study was to analyze the differences between knowledge, attitude, practice, blood sugar fasting and 2 hours post prandial (PP) of diabetic patients.  Methods: This experimental research using randomized control group pretest posttest design. Sample used 30 persons divided into 2 groups. Motivation and education are given 4 times in period of 1 month by visiting to the patient’s house. Data were collected by questionnaires and observation then analyzed by wilcoxon with α < 0.05.Results: Results showed that after intervention, treatment group who haved good knowledge were 15 persons (100%), good attitude were 8 persons (53.3%), moderate were 7 persons (46.7%), good practice were 11 persons (73.3%), moderate were 3 persons (20%) and less was 1 person (6.7%). Blood sugar fasting and 2 hours post prandial (PP) decreased were 13 persons (86.7%). Analysis using wilcoxon showed that result was significant.Conclusion: It can be concluded that motivation and education can improve knowledge, attitude, practice, decrease blood sugar fasting and 2 hours post prandial (PP). It was suggested to optimalized education and giving motivation due to improving support and awareness of patient to implement diabetes mellitus treatment.